The Role of Managerial Competencies in Enhancing Financial Performance of Governmental Service Organizations (Case Study: Public Hospitals in Yazd Province) - Ali Azhdari; Homayoon Eshkevargiry; Faezeh Abuei; Amir Mohammad Saadatmand; Mohammad Javad Abazari (مجله علوم پزشکی صدرا)
Introduction: The appointment of managers is one of the most critical decisions in any organization, and it should be based on the competencies of the managers. Managerial competencies at different levels in hospitals offer numerous benefits, including gaining a competitive advantage, strengthening teamwork behavior, and improving financial performance. This study aimed to investigate the role of managerial competencies in enhancing the financial performance of public hospitals in Yazd Province.Methods: This study was applied-developmental in terms of purpose and deductive in terms of approach. In terms of strategy, it was a descriptive-analytical study of the exploratory type, situated within the positivist paradigm. Data were collected using a questionnaire, and the study population comprised managers and supervisors of public hospitals in Yazd Province. Given the limited number of participants, the questionnaire was distributed to all members of the population. Out of 180 distributed questionnaires, 152 valid responses were collected. Data analysis was conducted using Smart PLS3 and SPSS 25 software.Results: The results indicated that managerial competencies, specifically in the individual, technical, and interactive dimensions, had a direct and significant effect on the financial performance of hospitals.Conclusion: Selecting competent managers for decision-making related to resource allocation, control, and the efficient utilization of resources can enhance the financial performance of hospitals. Furthermore, it could improve managerial accountability in performance evaluation and help achieve objectives in line with the accreditation standards of public hospitals in Yazd Province.